The influence of social isolation resulting from the COVID-19 pandemic on the mental health of pregnant women: literature review (Research, Society and Development, 2021)
Pregnant women may represent a vulnerable group to infection by COVID-19, due to immunological imbalance at the maternal-fetal interface. For this reason, this study carried out an integrative literature review in order to identify how recently published scientific papers have addressed the relationship between social isolation - caused by COVID-19 - and the mental health of pregnant women. This is an integrative literature review, in which articles published from 2020 to 2021 were analyzed, selected based on their relevance and updated information. The study of literature published in Portuguese was prioritized, as Brazil is one of the countries most impacted by the coronavirus. It was identified that social isolation due to COVID-19 caused psychological problems such as anxiety and depression in most pregnant women. There was a need for an early treatment for pregnant women, associating the use of drugs with psychotherapy. It was evident that educational campaigns on social networks and support services for this vulnerable group, via virtual means and via telephone, contributed to minimizing the impacts of the pandemic on the mental health of these women. As it is a recent theme and still under study by the scientific community, there is a need for a more detailed investigation by researchers on the impacts of social isolation on the mental health of pregnant women. However, it is clear that this public has been impacted by the COVID-19 pandemic and that emergency measures need to be taken to reverse this situation.